Achievements of the Compendium Bencao Tujing (Illustrated Classic of Materia Medica): A Preliminary Study - Lin-Lin Xiu; Shi-Chun Xu; Qi-Xuan Wang; Shao-Hong Chen; Hai-Yan Liu; Gan-Sheng Zhong; Su Lin (Wolters Kluwer Health/LWW, 2022)
Abstract. Bencao Tujing (Illustrated Classic of Materia Medica) is a brilliant and monumental compendium of materia medica by Su Song, which was published in 1061 and gathered ancestral knowledge from the Song dynasty as a legacy for posterity. The compendium emphasized the clinical applications of medicinal materials collected nationwide, which used illustrated atlases as references. The descriptions for each medicinal material subsumed the prescriptions containing it and were supplemented with relevant medical cases. Medical prescriptions predating the Song dynasty were included, which enhanced the clinical usefulness of the pharmacopoeia. The ancestral knowledge of materia medica was extensively merged with natural history throughout the compendium, which also made extensive reference to more than 200 Chinese classics, local gazetteers, and published works from the social and natural sciences. The inclusion of natural history and literature works changed the convention used in earlier pharmacopoeias to present medicines based solely on pharmacological analyses. The compendium also pioneered the inclusion of natural history in pharmacopoeia. Bencao Tujing helped establish China's leading position in the field of materia medica. Su Song's meticulous nature, truth-seeking attitude, and adherence to scientific thinking are truly worthy of emulation and promotion.